Notary's Responsibility As An Auction Official Ii In Facing The Opportunities And Challenges Of Auction Implementation Based On The Theory Of Authority - Bandhar Bandhar; Rasji Rasji (PT Publikasiku Academic Solution, 2023)
This article discusses the Roles and Responsibilities of a Notary as a Class II Auction Officer. This is based on the fact that a notary can act in parallel with his duties as a Class II Auction Officer who is appointed by the Minister of Finance in accordance with the Minister of Finance Regulation Number 189/PMK.06/2017 concerning Class II Official Auctions. . However, it is prohibited to act as maker and/or auctioneer of Class II real estate outside the notary's residence. The power of a notary to make a list of auctions is difficult to do directly by a notary because he has to go through the stages of appointing a minister who is responsible for government affairs in the financial sector. This makes the notary's position vulnerable to litigation due to overlapping regulations. The research method in the article is an empirical legal research type. Normative legal research is legal research relating to the enactment or implementation of normative provisions, followed by research on legal events contained in these normative provisions. Documentation and compliance with auction law regulations and auction commissioners. This includes the principles of publicity and fairness, and the obligation to act honestly, thoroughly, independently, and impartially